2021
DOI: 10.1007/s00261-021-02994-0
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Fontan-associated liver disease assessed by MRI and US in young adolescents

Abstract: Purpose Patients with Fontan circulation are at risk of developing hepatic fibrosis/cirrhosis. The mechanisms and disease development are unclear and early secondary liver cancer is a concern. This study will describe hepatic imaging findings in a national cohort of adolescents with Fontan circulation. Methods The patients prospectively underwent abdominal contrast enhanced magnetic resonance imaging (MRI) including diffusion-weighted imaging. Images were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 46 publications
1
22
1
Order By: Relevance
“…However, it is in contrast to the findings of Thrane et al [32], where only 28.6% of patients showed heterogeneous contrast enhancement on MRI. The low incidence of abnormal contrast enhancement in the study of Thrane et al [32] may be related to the injection of contrast medium for time-resolved angiography before dynamic liver MRI so, by the time of the dynamic liver MRI, there may already have been some equilibrium phase hepatic enhancement obscuring reticular hypoenhancement. The fact that all enhancement abnormalities in our study eventually became isointense to surrounding liver parenchyma on successive dynamic images supports the theory that these areas of hypoenhancement are related to delayed perfusion of parenchyma surrounding the small hepatic veins, similar to a Budd-Chiari-type phenomenon.…”
Section: Hepatic Reticular Hypoenhancement Is Universal and Is Likely Related To Hepatic Congestion And/ Or Fibrosiscontrasting
confidence: 96%
See 1 more Smart Citation
“…However, it is in contrast to the findings of Thrane et al [32], where only 28.6% of patients showed heterogeneous contrast enhancement on MRI. The low incidence of abnormal contrast enhancement in the study of Thrane et al [32] may be related to the injection of contrast medium for time-resolved angiography before dynamic liver MRI so, by the time of the dynamic liver MRI, there may already have been some equilibrium phase hepatic enhancement obscuring reticular hypoenhancement. The fact that all enhancement abnormalities in our study eventually became isointense to surrounding liver parenchyma on successive dynamic images supports the theory that these areas of hypoenhancement are related to delayed perfusion of parenchyma surrounding the small hepatic veins, similar to a Budd-Chiari-type phenomenon.…”
Section: Hepatic Reticular Hypoenhancement Is Universal and Is Likely Related To Hepatic Congestion And/ Or Fibrosiscontrasting
confidence: 96%
“…Our findings are in line with previous studies showing abnormal liver enhancement in most patients with Fontan palliation and in patients with other causes of congestive hepatopathy [29,31]. However, it is in contrast to the findings of Thrane et al [32], where only 28.6% of patients showed heterogeneous contrast enhancement on MRI. The low incidence of abnormal contrast enhancement in the study of Thrane et al [32] may be related to the injection of contrast medium for time-resolved angiography before dynamic liver MRI so, by the time of the dynamic liver MRI, there may already have been some equilibrium phase hepatic enhancement obscuring reticular hypoenhancement.…”
Section: Hepatic Reticular Hypoenhancement Is Universal and Is Likely Related To Hepatic Congestion And/ Or Fibrosissupporting
confidence: 92%
“…Another study of 35 patients, US detected only 17% of nodules that were found at MRI. [96,108,109] Cross-sectional F I G U R E 4 A 20-year-old female with complex congenital heart disease who had undergone the Fontan procedure. MRI images showing heterogeneous texture of the liver and heterogeneous enhancement due to congestive changes from the Fontan circulation.…”
Section: Characteristics Of Liver Nodules In Faldmentioning
confidence: 99%
“…Another study of 35 patients, US detected only 17% of nodules that were found at MRI. [ 96,108,109 ] Cross‐sectional imaging, particularly MRI, has the additional advantage of better characterizing nodules for guiding further management.…”
Section: Diagnosis Of Faldmentioning
confidence: 99%
“…Liver nodules are frequently detected in patients with FALD. 39,43,55,[65][66][67][68][69] In the only prospective study conducted to date, the prevalence of hepatic nodules was as high as 50%, and they were usually small (< 2 cm), multiple, and located in the periphery of the liver. 40 Postmortem series and biopsy studies have shown that most of these lesions correspond to focal nodular hyperplasia (FNH) or benign regenerative nodules.…”
Section: Hepatic Nodules and Hepatocellular Carcinomamentioning
confidence: 99%